The Future of TEFL in Universities in Indonesia: Trends and Innovations - Asrifan, Andi; Anita Candra Dewi; Tuti Wijayanti (ETERNAL (English, Teaching, Learning and Research Journal), 2024)
This article examines Indonesian universities and colleges' TEFL trends, difficulties, and innovations. With English as a worldwide language, the study emphasizes the necessity of English language education in Indonesia, especially in higher education. It addresses the use of technology in TEFL, the trend toward communicative language instruction, and the concentration on teaching English for specific reasons. Following a comprehensive examination and analysis, the study concluded that although online resources for language and culture learning are growing in popularity, educators especially those with greater experience continue to face challenges in successfully incorporating technology into their lessons. The survey looks at how students feel about TEFL programs, how they feel about using technology to learn languages, and how they feel about how it affects their ability to communicate across cultures. In order to enhance TEFL instruction and technology pedagogical topic understanding, the study also places a strong emphasis on teacher professional development. The report recommends that Indonesian colleges and institutions improve their TEFL programs in light of these facts. These include innovative instructional strategies, upgrades to facilities, and teacher preparation courses that use technology. These concepts educate language, intercultural communication, and global citizenship with the goal of enhancing TEFL instruction in Indonesia.